2021
DOI: 10.1080/19390211.2021.1958120
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Nutritional Supplement Use in Children with Tourette Syndrome

Abstract: Very little is known about the use of nutritional supplements in children with Tourette syndrome. The current study aimed to address the frequency of nutritional supplements and the use of special diets in children with Tourette syndrome and typically developing children. Additional data also sought to address the motivations behind using them, their cost and perceived benefits. A total of 76 responses from an anonymous online survey (Tourette syndrome = 42; typically developing = 34) were completed and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Mantel et al [36] also described benefits in the reduction of tics after the incorporation of nutritional and dietary changes [36]. Another recent study conducted on children with TS compared with typically developing (TD) children demonstrated a clinical improvement in 75% of supplement users in the TS group, mainly in motor and vocal tics, sleep quality and anxiety reduction [37]. Other studies have reported the beneficial effects of vitamin B6 and nutritional supplements in the treatment of ASD [26,27,38].…”
Section: Discussionmentioning
confidence: 99%
“…Mantel et al [36] also described benefits in the reduction of tics after the incorporation of nutritional and dietary changes [36]. Another recent study conducted on children with TS compared with typically developing (TD) children demonstrated a clinical improvement in 75% of supplement users in the TS group, mainly in motor and vocal tics, sleep quality and anxiety reduction [37]. Other studies have reported the beneficial effects of vitamin B6 and nutritional supplements in the treatment of ASD [26,27,38].…”
Section: Discussionmentioning
confidence: 99%